Effectiveness of conservative treatment for patellofemoral pain syndrome: A systematic review and meta-analysis - Mikhail Saltychev; Rebecca A. Dutton; Katri Laimi; Gary S. Beaupre; Petri Virolainen; Michael Fredericson (FOUNDATION REHABILITATION INFORMATION, 2025)
Objective: To evaluate the evidence regarding the effectiveness of conservative treatment in reducing patellofemoral pain.Data sources: CENTRAL, MEDLINE, CINAHL, and PE-Dro databases.Study selection: Adults with patellofemoral pain, randomized controlled trials only, any conservative treatment compared with placebo, sham, other conservative treatment, or no treatment. Two independent reviewers.Data extraction: Data were extracted from the full-text of the articles, based on Cochrane Collaboration recommendations. The outcome of interest was the difference between groups regarding change in pain severity.Data synthesis: The majority of studies were underpowered. More than 80% of the 37 trials did not show a clinically significant benefit. Clinically significant effects of different sizes were found for 7 trials (6 studies out of 7 had short follow-ups). These effects were found for: (i) pulsed electromagnetic fields combined with home exercise -33.0 (95% CI -45.2 to -20.8); (ii) hip muscle strengthening -65.0 (95% CI -87.7 to -48.3) and -32.0 (-37.0 to -27.0); (iii) weight-bearing exercise -40.0 (95% CI -49.4 to -30.6); (iv) neuromuscular facilitation combined with aerobic exercise and stretching -60.1 (95% CI -66.9 to -54.5); (v) postural stabilization -24.4 (95% CI -33.5 to -15.3); and (vi) patellar bracing -31.6 (95% CI -35.2 to -28.0).Conclusion: There is no evidence that a single treatment modality works for all patients with patellofemoral pain. There is limited evidence that some treatment modalities may be beneficial for some subgroups of patients with patellofemoral pain.